2015
DOI: 10.1093/infdis/jiv206
|View full text |Cite
|
Sign up to set email alerts
|

CCL20 Displays Antimicrobial Activity AgainstCryptosporidium parvum, but Its Expression Is Reduced During Infection in the Intestine of Neonatal Mice

Abstract: CCL20 is a chemokine with antimicrobial activity. We investigated its expression and role during neonatal cryptosporidiosis, a worldwide protozoan enteric disease leading to severe diarrhea. Surprisingly, during infection by Cryptosporidium parvum, CCL20 production by the intestine of neonatal mice is reduced by a mechanism independent both of the enteric flora and of interferon γ, a key cytokine for the resolution of this infection. However, oral administration of recombinant CCL20 to neonatal mice significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…Animal models for exploring C. parvum infection in vivo are limited, the majority of which use neonatal or immunosuppressive hosts (2729). We have previously reported a model in the weaned malnourished mouse that more closely mimics the complex interaction between the normal immune response and pathogen (13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models for exploring C. parvum infection in vivo are limited, the majority of which use neonatal or immunosuppressive hosts (2729). We have previously reported a model in the weaned malnourished mouse that more closely mimics the complex interaction between the normal immune response and pathogen (13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dysregulation of the intestinal barrier function is not only observed in response to infection by a broad diversity of enteric pathogens such as Clostridium perfringens, Escherichia coli, Salmonella, rotavirus, but also in inflammatory bowel disease (IBD) such as Crohn's or celiac diseases (Guttman and Finlay, 2009;Suzuki, 2013). Recently, several studies have been performed to decipher the immune and inflammatory mechanisms such as immune cell recruitment and production of immune mediators including antimicrobial peptides, and cytokines involved in the control of C. parvum infection (Laurent et al, 1997;Chen et al, 2007;Guesdon et al, 2015). We recently identified the key importance of innate immunity and more particularly of dendritic cells in the resolution of the acute phase of the infection (Lantier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This group also found that another miRNA, miR-221, regulated ICAM-1 expression during C. parvum infection, possibly as a means to enhance lymphocyte homing to sites of infection (77). Lastly, two chemokines mentioned previously, CX3CL1 and CCL20, were also found to be regulated by miRNAs during C. parvum infection (43,44). CX3CL1 is negatively regulated by miR-424 and miR-503, whereas CCL20 is negatively regulated by miR-21.…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 60%
“…In response to infection, IECs secrete chemokines and cytokines such as IL-8, CXCL10, and CCL2 responsible for the recruitment of inflammatory cells and activation of adaptive immune cells (30,37,38); prostaglandins that enhance intestinal fluid secretion (39); and AMPs like β-defensins, which are capable of directly killing sporozoites in vitro (40). Recently, it was shown that CCL20, a chemokine (41) and AMP (42) secreted in part by IECs in the intestine, was down regulated during Cryptosporidium infection of neonatal mice (43)*. Furthermore, oral administration of recombinant CCL20 reduced parasite burden in a manner independent of immune cell recruitment, but rather via direct cytolytic activity on extracellular infective stages of the parasite.…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 99%
See 1 more Smart Citation